2D/3D Perovskite: A Step toward Commercialization of Perovskite Solar Cells. Issue 7 (16th February 2023) - Lin, Tao; Dai, Tingting; Li, Xiong
Abstract : Perovskite materials have demonstrated excellent performance in the field of solar cells, and the device efficiency has already exceeded 25%. However, to date, perovskite solar cells (PSCs) have not been able to achieve large‐scale production. The biggest obstacle to commercializing PSCs is the stability problem that has been widely criticized since their inception. In the last 5 years, the emergence of 2D/3D perovskites has provided a new way to solve this problem. In this review, the representative work on 2D/3D perovskites is summarized, focusing on how 2D/3D structures can simultaneously improve device efficiency and stability. Starting from materials, the current perovskite material system with 2D/3D structure, as well as the bulky organic molecules used to prepare 2D/3D perovskites, is summarized and the corresponding preparation methods are discussed. After that, the influence of the 2D/3D structure on the crystallization of perovskites, the passivation, stabilization, and protection of 2D perovskite on 3D perovskite, and the mechanism of the 2D/3D perovskite heterojunction are discussed in depth. In the end, the development of 2D/3D perovskite from the aspects of research status, advantages, problems encountered, and future research directions is analyzed and prospected. Abstract : The preparation of 2D/3D perovskite as the optoelectronic material for perovskite solar cells has gradually become an important means to solve the problem of device stability. This review systematically summarizes and discusses the mechanism of 2D/3D structure improving the efficiency and stability of devices from materials to structures to optoelectronic properties.